Cross-layer design of coding operation and rate selection for network coding-based multihop wireless network - Kaikai Chi; Xiaohong Jiang; Horiguchi, S. (2009 Fourth International Conference on Communications and Networking in China, 2009)
Network coding has the potential to greatly improve the throughput of wireless networks. In the current proposals for wireless network coding, network nodes transmit packets at a fixed transmission rate. It is notable, however, that by dynamically selecting the rate we can effectively improve the node transmission efficiency. In this paper, we study the application of rate-adaptive transmission mechanism in network coding-based multihop wireless networks. In such networks, whether a coding solution is satisfactory depends not only on the number of involved native packets, but also on the packet loss probabilities of intended nexthops and the transmission time, both of which depend on the transmission rate. Therefore, we propose an efficient algorithm for jointly finding the good combinations of coding solution and transmission rate. Simulation results demonstrate that compared to the rate-fixed transmission, the rate-adaptive transmission based on our algorithm can significantly improve the node transmission efficiency.